Catheter-related right atrial thrombosis from malpositioned totally implantable venous access ports: Case series and preventive lessons - Yanshou Zhang; Fangyi Sun; Chao Yang; Weina Wang; Shuo Zhang; Xiaolong Li; Yunjiang Liu (SAGE Open Medical Case Reports)
Totally implantable venous access ports are widely used for long-term intravenous therapy in oncology patients. However, catheter malpositioning may result in catheter-related right atrial thrombosis, a rare but potentially life-threatening complication. We report three breast cancer patients who developed catheter-related right atrial thrombosis due to deeply located catheter tips within the mid-right atrium. All patients were successfully treated with systemic thrombolysis combined with anticoagulation, resulting in complete thrombus resolution. These cases underscore the preventable nature of catheter-related right atrial thrombosis through accurate intraoperative catheter tip localization using intracavitary electrocardiography or echocardiography and highlight the limitations of relying solely on postprocedural chest radiographs. Early recognition, precise localization, and individualized treatment are essential, but prevention remains the cornerstone of safe totally implantable venous access port utilization.